Epsins Regulate Mouse Embryonic Stem Cell Exit from Pluripotency and Neural Commitment by Controlling Notch Activation. (25th February 2019) - Cardano, Marina; Zasso, Jacopo; Ruggiero, Luca; Di Giacomo, Giuseppina; Marcatili, Matteo; Cremona, Ottavio; Conti, Luciano
Abstract : Epsins are part of the internalization machinery pivotal to control clathrin-mediated endocytosis. Here, we report that epsin family members are expressed in mouse embryonic stem cells (mESCs) and that epsin1/2 knockdown alters both mESC exits from pluripotency and their differentiation. Furthermore, we show that epsin1/2 knockdown compromises the correct polarization and division of mESC-derived neural progenitors and their conversion into expandable radial glia-like neural stem cells. Finally, we provide evidence that Notch signaling is impaired following epsin1/2 knockdown and that experimental restoration of Notch signaling rescues the epsin-mediated phenotypes. We conclude that epsins contribute to control mESC exit from pluripotency and allow their neural differentiation by appropriate modulation of Notch signaling.